2019
DOI: 10.21037/apm.2019.08.09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on post-operative recovery and mental status in patients receiving robotic-assisted thoracic surgery

Abstract: Background: This study aimed to investigate the effects of dexmedetomidine on the post-operative recovery and mental status in patients receiving robotic-assisted thoracic surgery (RATS).Methods: One hundred patients who received selective RATS under general anesthesia were recruited and assigned into control group (C) and dexmedetomidine group (D). The anesthesia induction and maintenance were consistent between groups. Midazolam, sufentanil, propofol and rocuronium were intravenously injected for anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In 2017, Xue Li [17] found that the incidence of PPCs (including pulmonary infection, pneumothorax and pleural effusion) tended to be lower in the DEX group than in the control group (OR 0.51, 95% CI 0.26 to 1.00; p = 0.050) in elderly patients after cardiac surgery. In 2019, Li-Yun Zhang [18] indicated that there were no significant differences in PPCs(including atelectasis, pneumonia and air leak) between DEX and control groups (P > 0.05) in patients receiving roboticassisted thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Xue Li [17] found that the incidence of PPCs (including pulmonary infection, pneumothorax and pleural effusion) tended to be lower in the DEX group than in the control group (OR 0.51, 95% CI 0.26 to 1.00; p = 0.050) in elderly patients after cardiac surgery. In 2019, Li-Yun Zhang [18] indicated that there were no significant differences in PPCs(including atelectasis, pneumonia and air leak) between DEX and control groups (P > 0.05) in patients receiving roboticassisted thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that DEX could attenuate perioperative stress, inflammation, and protect the immune function of surgical patients [12], and can provide clinically postoperative pulmonary relevant benefits by improving oxygenation and lung mechanics [13,14], all of which may contribute to decreased postoperative complications and improved clinical outcomes. In the last few years, a few clinical trials have evaluated the effect of DEX on PPCs [13][14][15][16][17][18][19]. However, the results of these studies are markedly variable and appear to be underpowered.…”
Section: Introductionmentioning
confidence: 99%
“…In present study, when etomidate was combined with dexmedetomidine, the time to spontaneous respiration, time to recovery and tracheal extubation time were prolonged. However, intraoperative intravenous infusion of dexmedetomidine (0.4 μ/kg/h) did not affect postoperative anesthesia recovery in patients undergoing thoracic surgery 27 , or provided faster recovery in patients undergoing tympanoplasty surgery 28 . It was suggested that the administeration of dexmedetomidine in long-term surgery rather than short-term surgery could provide faster recovery.…”
Section: Discussionmentioning
confidence: 89%
“…[ 9 10 ] The use of dexmed has been studied extensively in laparoscopic surgeries;[ 11 12 13 ] however there is limited but growing data with the use of dexmed in robotic surgeries. [ 14 15 ] Though one may argue that the principles of laparoscopic surgery can be extrapolated to robotic surgery, one must understand that there remains a difference in the two surgical approaches. Literature has shown in addition to the need of steeper positions,[ 16 ] robotic surgeries have prolonged duration and more opioid use when compared to their laparoscopic counterparts.…”
Section: Discussionmentioning
confidence: 99%